Mindfulness-based cognitive therapy in patients with depression: current perspectives - MacKenzie MB; Abbott KA; Kocovski NL (Neuropsychiatric Disease and Treatment, 2018)
Meagan B MacKenzie,1 Kayleigh A Abbott,2 Nancy L Kocovski2 1Department of Psychology, Ryerson University, Toronto, ON, Canada; 2Department of Psychology, Wilfrid Laurier University, Waterloo, ON, Canada Abstract: Mindfulness-based cognitive therapy (MBCT) was developed to prevent relapse in individuals with depressive disorders. This widely used intervention has garnered considerable attention and a comprehensive review of current trends is warranted. As such, this review provides an overview of efficacy, mechanisms of action, and concludes with a discussion of dissemination. Results provided strong support for the efficacy of MBCT despite some methodological shortcomings in the reviewed literature. With respect to mechanisms of action, specific elements, such as mindfulness, repetitive negative thinking, self-compassion and affect, and cognitive reactivity have emerged as important mechanisms of change. Finally, despite a lack of widespread MBCT availability outside urban areas, research has shown that self-help variations are promising. Combined with findings that teacher competence may not be a significant predictor of treatment outcome, there are important implications for dissemination. Taken together, this review shows that while MBCT is an effective treatment for depression, continued research in the areas of efficacy, mechanisms of action, and dissemination are recommended. Keywords: mindfulness-based cognitive therapy, MBCT, major depressive disorder, efficacy, mechanisms of action, dissemination